Fruit production under different environmental and management conditions of argan, Argania spinosa (L.) - Zunzunegui, M; Ain-Lhout, F; Jáuregui, J; Díaz Barradas, M C; Boutaleb, S; Álvarez-Cansino, L; Esquivias, M P (Journal of Arid Environments, 2010)
The study’s aim was to evaluate the effects of different management and environmental conditions on fruit and seed mass production of Argania spinosa, an endemic tree to Morocco that grows in arid and semiarid areas and is now undergoing a protracted regression due to overexploitation. Four study areas with different herbivory intensity, altitude and climatic conditions were selected. In each one the following measurements were carried out in 20 trees: tree and crown height, crown projection, trunk diameter, leaf area index, tree density, fruit production$m3 , number of fruits per tree, fruit, endocarp and kernel mass and seed size. The greatest fruit production and fruit size were found in populations with better climatic conditions, followed by the population under high human pressure. The lowest fruit production and fruit size were found in the population under the most severe climate conditions. Mean kernel mass was not affected by harsh climatic conditions or high human pressure, but when both stressing factors were combined all measured fruit traits were abated. Although A. spinosa is tolerant to high herbivory pressure, this perturbation induces a drastic decrease in fruit production. Managing plans addressing its reintroduction and/or maintenance should include a conservative strategy controlling herbivory
Keywords: herbivory; Kernel mass; leaf area index; Oil content; Oil production; seed mass

Plant functional types and ecosystem function in Mediterranean shrubland - Barradas, Díaz; Zunzunegui, M (Journal of Vegetation Science, 1999)
This study attempts to identify Plant Functional Types (PFTs) within the scrub vegetation of the stabilized sand dunes of the Doñana National Park (southwestern Spain) and to explore possible links with ecosystem function. Two 10-km long transects were sampled along a gradient of water table depth from elevated and dry dunes to a border area close to the salt marsh. A matrix of cover values for 20 woody species × 58 plots and a matrix of 24 morphological and physiological traits × 20 species were analysed by means of DCA and TWINSPAN to identify the main vegetation types and PFTs. In order to know the predominant plant traits, the matrix of 20 species × 58 plots was multiplied by the 24 traits × 20 species matrix. The resulting 24 traits × 58 plots matrix was analysed by means of DCA. The main vegetation types coincide with the previous descriptions of the Park with Juniperus phoenicea woodland and xerophytic species dominating the top of the dunes and hygrophytic species with isolated Quercus suber trees in the depressions. Previous classifications of Mediterranean woody plants resulted in two main PFTs. The present analysis confirmed these two groups: maquis versus garrigue, but added four new groups. The analysis of the traits × plots matrix revealed that the main trend of variation is related to the water table gradient, while the traits related to the species of mature plant communities had little weight in the analysis because these communities are restricted to isolated patches.
Keywords: Doñana; Plant trait; Regeneration; water potential; Water table depth